Clinical characteristics and outcomes in hospitalized adult influenza patients: an observational study from Norway 2014–2018. Issue 5 (4th May 2022) - Wæhre, Torgun; Tunheim, Gro; Bodin, Johanna Eva; Laake, Ida; Kvale, Dag; Kran, Anne-Marte Bakken; Brekke, Hanne; Løken, Ragnhild; Oftung, Fredrik; Mjaaland, Siri; Dyrhol-Riise, Anne Margarita
Abstract: Background: Seasonal influenza causes substantial numbers of hospitalizations annually. We have characterized the clinical picture and treatment practice in hospitalized adult influenza patients and assessed whether clinical risk scores on admission or influenza type were associated with severe outcomes. Methods: Clinical characteristics and risk scores on admission (CRB65, CRB, SIRS and q uick S equential O rgan F ailure A ssessment [qSOFA]), treatment and severe outcomes (defined as: stay in intensive care unit (ICU), receiving oxygen supplementation or staying ≥5 days in hospital), were recorded in patients hospitalized with influenza at Oslo University Hospital, Norway, between 2014 and 2018. Results: Among the 156 included patients, 52.6% had influenza A(H3N2), 32.6% influenza B and 12.8% influenza A(H1N1). Median age was 70 years and 59.6% of patients were ≥65 years. Nine (5.8%) of the patients were treated in ICU, 43.0% received oxygen and 47.4% stayed ≥5 days in hospital. Overall, 34.6% of the patients had a high CRB score on admission which was associated with stay in ICU and oxygen supplementation. Multivariate analyses identified age, and pneumonia (46.8%), but not influenza type, to be associated with severe outcomes. Antiviral treatment was given to 37.2% of the patients, while 77.6% received antibiotics. Only 25.5% of patients with influenza B received antiviral therapy. Conclusions: The influenza patients were mostly elderly, and few patients were treated in ICU. A high CRB score was associated with severe outcomes with possible implications for patient monitoring. Less than 40% of the patients received antiviral therapy, whereas the majority were treated with antibiotics, indicating potential for optimising treatment strategies.